Dynamics of hepatitis B virus quasispecies heterogeneity and virologic response in patients receiving low‐to‐moderate genetic barrier nucleoside analogs. Issue 4 (15th November 2012) - Peveling‐Oberhag, J.; Herrmann, E.; Kronenberger, B.; Farnik, H.; Susser, S.; Sarrazin, C.; Zeuzem, S.; Hofmann, W.‐P.
Summary We characterized the early dynamics of hepatitis B virus (HBV) quasispecies evolution during the first weeks of antiviral therapy with low‐to‐moderate genetic barrier antiviral drugs and associated these data with antiviral response patterns. Fifteen chronic hepatitis B patients (men, 10; mean age, 34; HBeAg positive, 6) who received lamivudine or telbivudine for at least 52 weeks were included. HBV DNA was extracted from serum, and a 910‐bp fragment covering domains A–F of the reverse transcriptase region was amplified, cloned and sequenced. Parameters of quasispecies heterogeneity, genetic diversity and complexity were calculated and were correlated with complete virologic response, defined as undetectable HBV DNA at week 52. Nine patients achieved complete virologic response during the observational period. While baseline HBV DNA levels and HBeAg status were associated with virologic response, baseline quasispecies complexity and diversity of responders showed no significant difference to those of nonresponders (P > 0.05). However, at week 4, quasispecies complexity of nonresponders was significantly higher compared with that of responders on the nucleotide level (P = 0.01) and the aa level (P = 0.04). The number of synonymous substitutions per synonymous site dropped significantly in responders at week 4 (P = 0.04), while there was no difference in nonresponders. The HBV quasispecies complexity at the early stage of antiviral therapy (week 4) with the low‐to‐moderate genetic barrier nucleoside analogs lamivudine or telbivudine was associated with subsequent virologic response. Further studies are needed to confirm HBV quasispecies evolution as additional predictive marker for beneficial treatment outcome.